2017
DOI: 10.1108/ijopm-09-2015-0556
|View full text |Cite
|
Sign up to set email alerts
|

The role of geographical distance and its efficacy on global purchasing practices

Abstract: Purpose The purpose of this paper is to investigate the extent to which the geographical location of and thus the geographical distance between buyer and supplier impact on the efficacy of purchasing practices (i.e. strategic purchasing management, tactical purchasing management, relational purchasing management) in terms of operational performance. Design/methodology/approach The authors utilise cross-country data collected through the International Purchasing Survey group across a variety of countries and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Therefore, the results may be biased; for example, in Eastern Europe, the processes may occur differently, not to mention in an Asian culture. This is in line with previous research has found that the purchasing practices can be influenced by differences in geographical location (Wiengarten and Ambrose, 2017). Thus, future research might thus investigate region-specific factors for the emergence of SDM archetypes, as well as the types of decision-making in smaller companies.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the results may be biased; for example, in Eastern Europe, the processes may occur differently, not to mention in an Asian culture. This is in line with previous research has found that the purchasing practices can be influenced by differences in geographical location (Wiengarten and Ambrose, 2017). Thus, future research might thus investigate region-specific factors for the emergence of SDM archetypes, as well as the types of decision-making in smaller companies.…”
Section: Discussionsupporting
confidence: 93%
“…In such firms, a large and varied supply base is not purely seen as an administrative burden (Bode and Wagner, 2015; Choi and Krause, 2006), but rather as a strategic asset that reduces dependency and gives more flexibility in case of supply disruptions (Birkie and Trucco, 2020). Furthermore, such a long-term focus requires the adoption of a more proactive approach and having purchasing strategies that integrate risk and uncertainty into supply base management practices (Paulraj et al , 2006; Wiengarten and Ambrose, 2017). Since firms with a strategic purchasing function are more likely to identify SBC as a source of potential supply risk, they are also more likely to develop proactive approaches for managing the challenges of SBC and to assess its impact on a range of performance outcomes.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Applied research in culture has identified the role of national culture in organizational performance and specific organizational actions (Garg and Ma, 2005). This research includes studies regarding the analysis of product recall announcements in the US Food and Drug Administration enforcement report (Cheah et al , 2007) as well as studies suggesting culture impacts whether an organization takes responsibility, offers an excuse or directs the blame elsewhere (Wiengarten and Ambrose, 2017). Mathews et al (2001) note that managerial approaches to problems typically mirror the home culture.…”
Section: Literature Review and Model Developmentmentioning
confidence: 99%